Earth Quake Model 2.0 : Attract Force Equation Release Earthquake Mechanism with Explaining Related Phenomena (Global Journal of Science Frontier Research, 2019)
Earth quake was nature phenomena, which has huge destroyed power, and make huge economic loss and human injuries and deaths. The reason of Earth quake has caused lots of researches. And predicting Earthquake has been the very important work on every day. While the mechanism of Earth quake was still unclearly, and the Earthquake predictions were still at initial stage. This paper use attract force mathematic physics model to build Earthquake mechanism model by finite element method, and try to explain the reason of Earthquake formation. At same time it was used to explain the related phenomena about Earthquake. The aims were to help for accurate predict Earthquake, and try to redeem the economic loss and save more people. This model was named Earth Quake Model 2.0, which was different and distinguished from the models before, and it was wish to help for seismic researches.
Keywords: earth quake; mathematic model; attract force equation; seismic mechanism; explain phenomena